Building and Maintaining the TEI LingSIG Bibliography - Piotr Bański; Stefan Majewski; Maik Stührenberg; Antonina Werthmann (Journal of the Text Encoding Initiative)
The present contribution addresses an infrastructural issue of universal relevance, addressed in the specific context of the TEI. We describe a combination of open-source tools and an open-access approach to creating knowledge repositories that have been employed in building a bibliographic reference library for the “TEI for Linguists” special interest group (LingSIG). The authors argue that, for an initiative such as the TEI, it is important to choose open, freely available solutions. If these solutions have the advantage of attracting new users and promoting the initiative itself, so much the better, especially if it is done in a non-committal way: no one using the LingSIG bibliographic repository has to be a member of the LingSIG or a “TEI-er” in general.